The Association Between Cardiac Rehabilitation Attendance and Hospital Readmission. Issue 6 (November 2018) - House, Chad M.; Anstadt, Mary A.; Stuck, Logan H.; Nelson, William B.
Purpose: Cardiac rehabilitation is associated with improved clinical outcomes, but the impact of individual cardiac rehabilitation sessions on readmission rates is less studied.Methods: A retrospective evaluation of the relationship between the number of cardiac rehabilitation sessions completed and all-cause and cardiac readmission rates at 1 year was conducted. The 1-year cardiac readmission counts were modeled via Poisson regression.Results: Of the 347 patients included in the primary analysis, 227 (65%) completed all assigned cardiac rehabilitation sessions. At 1 year, 135 patients (39%) had at least 1 cardiac readmission, and 155 patients (45%) had at least 1 all-cause readmission. The primary result was that every additional cardiac rehabilitation session completed was associated with a 1.75% lower incidence rate of 1-year cardiac readmission (P = .01) and a 2% lower incidence rate of all-cause hospital readmission (P = .001).Conclusion: Regardless of the number of cardiac rehabilitation sessions assigned, each additional session attended was associated with reduced cardiac readmission by 1.75% and all-cause readmission by 2%.